2018
DOI: 10.1038/s41523-018-0065-7
|View full text |Cite
|
Sign up to set email alerts
|

Change in longitudinal trends in sleep quality and duration following breast cancer diagnosis: results from the Women’s Health Initiative

Abstract: Breast cancer survivors frequently report sleep problems, but little research has studied sleep patterns longitudinally. We examined trends in sleep quality and duration up to 15 years before and 20 years after a diagnosis of breast cancer, over time among postmenopausal women participating in the Women’s Health Initiative (WHI). We included 12,098 participants who developed invasive breast cancer after study enrollment. A linear mixed-effects model was used to determine whether the time trend in sleep quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…Overall, BC patients seem to have subtle but still present modifications of sleep architecture compared to HC. These results are in accordance with those of previous studies suggesting effects of cancer and/or diagnostic on sleep 32 , 33 . One may argue that the greater number of awakenings in patients could be driven by the effects of radiotherapy as most of our sample of patients was treated with radiotherapy following surgery.…”
Section: Discussionsupporting
confidence: 93%
“…Overall, BC patients seem to have subtle but still present modifications of sleep architecture compared to HC. These results are in accordance with those of previous studies suggesting effects of cancer and/or diagnostic on sleep 32 , 33 . One may argue that the greater number of awakenings in patients could be driven by the effects of radiotherapy as most of our sample of patients was treated with radiotherapy following surgery.…”
Section: Discussionsupporting
confidence: 93%
“…Younger age has been associated with increased sleep disturbance [ 15 , 22 – 24 ], although other studies have found no association between age and sleep disturbance in patients with breast cancer [ 1 ]. Additionally, a large ( n = 12,098) longitudinal study found that breast cancer diagnosis was not significantly related to decreased sleep quality compared to pre-diagnosis, although sleep quality continued to decrease over time [ 25 ]. This would indicate that study participants would report poorer sleep quality as they aged.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies of the ISI in oncology samples have not yet focused specifically on cancer survivors after treatment completion. This is a significant gap in the literature, as the growing population of cancer survivors is known to have unique physical and psychological vulnerabilities, including high rates of insomnia, even many years after treatment . To address this, our study examined the internal consistency reliability and factor structure (ie, statistical approach to describing variability among variables) of the ISI (English version) in a sample of cancer survivors after treatment completion.…”
Section: Introductionmentioning
confidence: 99%